The Chemistry of Oil and Petroleum Products - Abilova, G. R.; Acter, Thamina; Aeppli, Christoph; Alostad, Latifa; Alzarieni, Kawthar Z.; Banejee, Sanjoy; Barrow, Mark P.; Betancourt, Soraya S.; Borisov, Roman S.; Cañas, Jesus A.; Connock, Gregory T.; Downham, Rory P.; et al. (De Gruyter STEM., 2022)
This first publication devoted to the chemistry of oil and petroleum products covers the broad range of topics from heavy fuel oils, gasoline/diesel fuel, crude oils and (diluted) bitumen to today's research on asphaltenes. Recent methods are summarized and the large new groups of chemicals found in oils are identified as well as described in detail. The work points the way for a more complete understanding of the composition of petroleum.